2023
DOI: 10.31083/j.ceog5006115
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Abbreviated MRI Scanning Reveals a High Specificity and Sensitivity in Detecting Breast Cancer

Abstract: Background: Breast cancer (BC) is the most common malignancy and the leading cause of mortality among women. Various diagnostic tools for early diagnosis and tumor progression detection have helped patients receive precise and timely treatment. This meta-analysis aims to evaluate the accuracy of abbreviated magnetic resonance imaging (ABB-MRI) data in the diagnosis of BC. Methods: The Preferred Reporting Items for Systematic Reviews and Comparative Meta-Analysis for Diagnostic Test Accuracy (PRISMA-DTA) guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Eghtedari et al demonstrated that DWI with a b-value of 1000 s/mm 2 showed better sensitivity for lesion detection [ 22 ]. Zhou, B. et al reported that abbreviated MRI showed high sensitivity and specificity for the diagnosis of breast cancer, compared to full-scanning protocols [ 23 ]. However, few studies have compared the diagnostic performance of fused high-b-value DWI using unenhanced T1WI with that of abbreviated post-contrast-enhanced MRI [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eghtedari et al demonstrated that DWI with a b-value of 1000 s/mm 2 showed better sensitivity for lesion detection [ 22 ]. Zhou, B. et al reported that abbreviated MRI showed high sensitivity and specificity for the diagnosis of breast cancer, compared to full-scanning protocols [ 23 ]. However, few studies have compared the diagnostic performance of fused high-b-value DWI using unenhanced T1WI with that of abbreviated post-contrast-enhanced MRI [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%